The Effect of Unemployment Rate, Education Level and Total Population on Poverty in West Java Province - Diki Purnomo; Gadis Amelia Pohan; Salsabilah Nurul Izza (Indonesian Journal of Advanced Research, 2023)
Poverty is a problem that always arises faced by both developed and developing countries. This study aims to determine the effect of population, education level and unemployment rate on poverty in the cities of West Java Province. This type of research data uses secondary data, namely time series data from 2012-2021 and cross section data in 9 cities in West Java Province which were obtained from the West Java Central Bureau of Statistics. The analytical method used in this study is Panel Data Regression using the Eviews 9 analysis tool. The results show that population size has a negative and significant effect on poverty in the cities of West Java Province. Taken together, population size, education level and Unemployment rate affects poverty in the cities of West Java Province.